Voices of the Forest as Resistance: Reflections on the Brazilian Documentary Mata (INSÓLITA - Revista Brasileira de Estudos Interdisciplinares do Insólito, da Fantasia e do Imaginário, 2026)
This article proposes a reflection on the formation of a dispositif of resistance within the forest through the Brazilian documentary Mata. Guided by images and voices, the film seeks to bring forth the surviving traces of an environmental disaster shaped by the economic expansion of so-called “planted” eucalyptus forests. The methodological approach is grounded in social cartography as an axis of alliances, articulating the notion of ecocinema with the contributions of thinkers such as Ailton Krenak, Édouard Glissant, and Deleuze and Guattari.Key words:  Ecocinema; Resistance; Forest; Social Cartography; Brazilian Documentary